The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.bandc.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced reliance on habitual behavior is moderated by cortisol reactivity

Abstract: Instrumental learning, i.e., learning that specific behaviors lead to desired outcomes, occurs through goal-directed and habit memory systems. Exposure to acute stress has been shown to result in less goal-directed control, thus rendering behavior more habitual. The aim of the current studies was to replicate and extend findings on stress-induced prompting of habitual responding and specifically focused on the role of stress-induced cortisol reactivity. Study 1 used an established outcome devaluation paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
56
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 64 publications
12
56
1
1
Order By: Relevance
“…For instance, neuropsychological research has identified certain neural systems that appear to be relatively insensitive to changes in the current reward-value of an outcome, with the activity of these systems relating to the frequency of participants' overt selections of responses that yield now-devalued outcomes (Liljeholm, Dunne, & O'Doherty, 2015;Schwabe, Tegenthoff, Höffken, & Wolf, 2012;Soares et al, 2012;Tricomi et al, 2009; for a review, see Patterson & Knowlton, 2018). Research in this tradition also suggests that humans show more habitual responses when the goal-directed system is hindered (for example, by manipulations designed to produce ‗ego-depletion', Lin, Wood, & Monterosso, 2016); on related lines, it has also been suggested that acute stress can tilt the balance in favor of the habit system (Schwabe & Wolf, 2009;Smeets, van Ruitenbeek, Hartogsveld, & Quaedflieg, 2018)a result which mirrors findings from animal research (Braun & Hauber, 2013).…”
mentioning
confidence: 99%
“…For instance, neuropsychological research has identified certain neural systems that appear to be relatively insensitive to changes in the current reward-value of an outcome, with the activity of these systems relating to the frequency of participants' overt selections of responses that yield now-devalued outcomes (Liljeholm, Dunne, & O'Doherty, 2015;Schwabe, Tegenthoff, Höffken, & Wolf, 2012;Soares et al, 2012;Tricomi et al, 2009; for a review, see Patterson & Knowlton, 2018). Research in this tradition also suggests that humans show more habitual responses when the goal-directed system is hindered (for example, by manipulations designed to produce ‗ego-depletion', Lin, Wood, & Monterosso, 2016); on related lines, it has also been suggested that acute stress can tilt the balance in favor of the habit system (Schwabe & Wolf, 2009;Smeets, van Ruitenbeek, Hartogsveld, & Quaedflieg, 2018)a result which mirrors findings from animal research (Braun & Hauber, 2013).…”
mentioning
confidence: 99%
“…A four-stage instrumental learning task divided over two days was used to assess goal-directed and habitual behaviour (Smeets et al, 2019, see figure 1 panel A). Participants learned six Stimulus-Response-Outcome (S-R-O) associations by trial-and-error on day one (stage 1).…”
Section: Instrumental Learning Taskmentioning
confidence: 99%
“…Stress plays an important role in the development and maintenance of addictive behaviours (Brewer, Catalano, Haggerty, Gainey, & Fleming, 1998;Sinha, 2001;Sinha & Jastreboff, 2013). Particularly the hypothesis of stress-induced relapse within the context of instrumental learning has received substantial attention (Sinha, 2001), and the frequent observation that stress renders behaviour habitual (Quaedflieg, Stoffregen, Sebalo, & Smeets, 2019;Schwabe, Wolf, & Oitzl, 2010;Smeets, van Ruitenbeek, Hartogsveld, & Quaedflieg, 2019) provides a potential mechanism (see Schwabe & Wolf, 2011 for review).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations